Protein Hydrolysates and Mo-Biofortification Interactively Modulate Plant Performance and Quality of ‘Canasta’ Lettuce Grown in a Protected Environment - Leo Sabatino; Beppe Benedetto Consentino; Youssef Rouphael; Claudio De Pasquale; Giovanni Iapichino; Fabio D’Anna; Salvatore La Bella (Agronomy, 2021)
Since the use of protein hydrolysates (PHs) enhances overall plant performance and quality of vegetables, they might be considered as a toll to face a number of concerns essentially associated to the growing request of premium quality foodstuff realized in agreement with eco-friendly agriculture practices. Molybdenum (Mo) is considered a fundamental trace element for human body. Thus, its shortage determines several disorders mainly related to neurological lesion and esophageal cancer. Biofortification of fruiting and leafy vegetables is a promising tool to prevent Mo deficiency in the human diet. The current study was carried out to assess the interactive effect of plant-derived PHs and Mo dosage (0.0, 0.5, 3.0, and 6.0 µmol L−1) on yield, morphology, nutritional and functional features, and nitrogen indices of ‘Canasta’ lettuce. Head fresh weight (HFW), head height (HH), ascorbic acid, K, Mg, total chlorophyll, as well as nitrogen use efficiency (NUE) index were positively correlated to PHs application. Furthermore, ascorbic acid and total chlorophyll were also improved by Mo supply. A great improvement in terms of soluble solid content (SSC), total sugars, total phenolic, carotenoids, Mo and N concentrations, nitrogen uptake efficiency (UE), and nitrogen physiological efficiency (PUE) indices was recorded when PHs application was combined with the highest Mo dosage (6.0 µmol L−1). Consequently, our results suggest that Mo-biofortification and PHs application can positively modulate ‘Canasta’ lettuce plant performance and quality.